Relationship between Workplaces Stress, Job Satisfaction and Resilience among Nurses of Government and Private Hospitals - Wajeeha Komal; Sehar Aziz (Indus Journal of Social Sciences, 2025)
Health care sector is one of the most demanding areas of working for nursing professionals, stress at the workplace and job satisfaction are key issues that affect the performance of a nurse in the health care setting. The objective of this research was to investigate the role of stress and resilience and satisfaction with job contentment in nurses in government and private hospitals in Kotli, Azad Kashmir. A correlational descriptive research design was used where 50 registered nurses who work in either government (n = 25) or private (n = 25) facilities were sampled purposively. Self-administered questionnaires comprised the Connor-Davidson Resilience Scale were employed and data were analyzed using Pearson correlation coefficients and independent sample t tests. The results showed that resilience had a significant positive relationship with job satisfaction; results demonstrated that the more resilient the nurses were, the greater their satisfaction with their jobs. On the other hand, workplace stress was negatively correlated with job satisfaction were by high workplace stress impaired job satisfaction. The comparative analysis further highlighted sector-specific challenges: The study revealed that, while nursing in a government hospital, the stressors could be limited resources, large number of patients among others, while in a private hospital the stress could be high performance expectations and patient demands among others. The findings reaffirmed the significance of assertiveness as the capacity to shield oneself against organizational stress and as a predictor of self-reported job satisfaction. Coping mechanisms and staff wellness programs are the proposed approaches to enhance the employee mental health, job satisfaction and organizational viability of the nursing profession. In synthesis, this work develops important leads for developing intentional action to address workplace stress with the goal of bolstering nurses’ resourcefulness and resilience so that quality patient care can be maintained.